2019
DOI: 10.1007/s40123-019-00209-w
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Control from Recurring Non-Infectious Uveitic Macular Edema with 0.19 mg Fluocinolone Acetonide Intravitreal Implant – A Case Report

Abstract: In January 2013, a 54-year-old pseudophakic woman was referred to the ocular inflammation clinic with a diagnosis of panuveitis, already on oral cyclosporine (100 mg/day) since 2010. She was a monocular patient, with the left eye eviscerated due to trauma and secondary endophthalmitis in 1995. She had experienced similar recurring episodes between 2010 and 2013. Examination revealed best-corrected visual acuity (BCVA) of 20/200. The anterior segment revealed the presence of flare and absence of cells. Intraocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Therefore, although the FAc implant does not appear to be a curative treatment (though possibly the disease burns itself out in some patients), it offers excellent disease control and can prevent recurrences of inflammation over considerable periods of time. Indeed, the authors of a case report describing a patient with panuveitis who demonstrated sustained control of inflammation and macular oedema for at least 3 years after treatment with the FAc implant concluded that the “benefits may persist even after cessation of the direct anti-inflammatory effect of the implant” [ 8 ].
Fig.
…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, although the FAc implant does not appear to be a curative treatment (though possibly the disease burns itself out in some patients), it offers excellent disease control and can prevent recurrences of inflammation over considerable periods of time. Indeed, the authors of a case report describing a patient with panuveitis who demonstrated sustained control of inflammation and macular oedema for at least 3 years after treatment with the FAc implant concluded that the “benefits may persist even after cessation of the direct anti-inflammatory effect of the implant” [ 8 ].
Fig.
…”
Section: Main Textmentioning
confidence: 99%
“…PVOH has been used in many clinically approved products over the last few decades. For example, the Iluvien ® implant has been fabricated by using PVOH and silicone and used for macular edema [ 92 ]. In addition, PVOH has been found to be extensively applied in preclinical research for developing hydrogels, microspheres, and nanoparticles for various therapeutic purposes [ 86 ].…”
Section: Common Polymers In La Ddssmentioning
confidence: 99%
“…Meira et al . [ 71 ] used the dexamethasone implant in a 54-year-old monocular patient with pseudophakia with sympathetic ophthalmia, undergoing therapy with cyclosporine. Because the patient had recurrent cystoid macular edema, supplementation with a dexamethasone implant was performed.…”
Section: Management Of Sympathetic Ophthalmiamentioning
confidence: 99%